Produits monastiques, publicités et initiatives de certification en Grèce - Katerina Seraïdari (Communiquer)
This article analyzes the recent initiatives about the Kanon certification concerning the Orthodox world and, more precisely, Greece. It questions the role that the monastic products, but also the religious certifications (like halal, kosher and the Catholic brand Monastic), play in a new approach of economic realities. It examines the use of the religious imaginary by Greek advertising. The aim is to show how the recent demand for monastic products is linked to restoration promises of the economic equilibrium, consumerism becoming in this context not only an experience but also an act of engagement. Another issue treated in this framework, the possibility for the religious domain to redefine the priorities and principles of commercial exchanges.